Impact of Stress on Students’ Quality of Life and Academic Performance in Therapeutic Dentistry: Legal Regulation Aspects - Makhlynets, Nataliia; Kokoshko, Myroslava; Plaviuk, Lev; Kukurudz, Nataliia; Stasiuk, Nadiya (Actual Dentistry, 2026)
Aim: This study investigates the impact of heightened anxiety and chronic socio-emotional stress on the quality of life and academic performance of medical students during wartime in Ukraine. It evaluates the decline in practical skill acquisition at the Department of Therapeutic Dentistry of Ivano-Frankivsk National Medical University due to persistent psychological tension. The psycho-emotional challenges are analyzed through the lens of legal regulation, focusing on the state’s obligations to ensure health protection and safe learning conditions under martial law in accordance with national and international standards. Methods: The research design is based on a quantitative analysis of data obtained through an anonymous survey of 65 dental students. Psycho-emotional states were assessed using the Spielberger–Hanin State–Trait Anxiety Inventory (STAI) and a specialized questionnaire developed by the authors. Statistical analysis was performed using Student’s t-test to evaluate the reliability of results. Results and Discussion. The findings demonstrate a significant increase in anxiety levels among all respondents. STAI scores showed no statistically significant difference between second-year students (Group I; n = 31) and fourth-year students (Group II; n = 34) (p > 0.05). In more than 90% of respondents, anxiety scores exceeded 45 points, indicating high anxiety. Prolonged exposure to wartime conditions with elevated anxiety levels transforms into chronic stress, as confirmed by reduced motivation for learning and self-improvement due to persistent fears of losing loved ones or housing. Chronic stress negatively affects both mental and physical health, reduces quality of life, and impairs academic achievement. The study revealed a discrepancy between statutory guarantees of health protection and their practical implementation in the student environment. National healthcare and education policy should prioritize stress prevention and the creation of safe conditions for youth development. Strengthening the legal framework is essential to minimize the adverse effects of stress factors on the younger generation. Scientific Novelty. This is the first comprehensive study of the psycho-emotional state of dental students at Ivano-Frankivsk National Medical University under prolonged martial law. No significant differences in anxiety levels were found between junior and senior students, confirming the universal impact of chronic socio-emotional stress on medical education. The novelty lies in the integration of empirical medical data with a critical legal analysis of healthcare regulation. The study substantiates the role of legal mechanisms as tools for minimizing psycho-emotional risks that directly affect students’ health and academic performance. Conclusions. The results confirm the critical need to monitor and account for the psycho-emotional state of medical students in Ukraine under martial law. Anxiety is identified as a key determinant of effective learning and clinical competence formation. National healthcare and education policy must be imperatively directed toward systemic psychological support and the creation of safe learning conditions in higher education. A comprehensive approach to this issue aligns with international standards, particularly the UN Convention on the Rights of the Child and the International Covenant on Economic, Social and Cultural Rights, which guarantee the right to the highest attainable standard of health. Implementation of the proposed measures will mitigate the negative impact of socio-environmental stress and ensure a favorable environment for the professional development of future specialists.